學校管理模式與學生偏差行為關係之研究：以教師教學投入與教學支援為中介變項 Relationship Between School Management and Student Deviant Behavior: Pedagogical Input from Teachers and Teaching Support as Mediating Variables - 陳玉娟* Yu-Chuan Chen (National Taiwan Normal University, 2021)
本研究目的係在釐清學校管理模式、教師教學投入、教學支援及學生偏差行為的內涵，進而驗證此四個變項之間的關係、確認本研究所建構之結構方程模式與觀察資料間的適配程度與模式是否成立。為了達成上述研究目的，研究者利用經濟合作暨發展組織（Organization for Economic Co-operation and Development, OECD）於2015年進行之實證調查活動，請學校校長或是由校長所指定之學校人士，依目前所服務學校的實際狀況進行填答，共計回收有效問卷14,530份。研究者挑選符合變項定義之題項為衡量變項，利用IBM SPSS Statistic 22.0統計軟 體進行描述性統計、探究性因素分析及信度分析，並利用AMOS進行結構方程模式驗證，以瞭解本研究所建構之方程模式是否適配。研究結果發現，本研究的七項假設皆成立，且建構之 結構方程模式達到適配標準。綜言之，研究支持：一、學校管理模式對教師教學投入、教學支援及學生偏差行為有直接影響；二、教師教學投入對學生偏差行為具有直接影響效果；三、教學支援對於學生偏差行為亦具有直接影響效果；四、教師教學投入與教學支援亦扮演中介變數角色，學校管理模式可以利用前述兩者作為中介變數，間接影響學生偏差行為表現狀況。 立基於上述研究結果發現，本研究提出相關建議供參。 This study examined the implications of school management, pedagogical input from teachers, teaching support, and student deviant behavior to construct a structural equation model and validating it using with observational data. The researcher used the empirical data provided in 2015 by the Organization for Economic Co-operation and Development (OECD). The researcher asked the school principal or a person designated by the principal to complete a questionnaire, and 14,530 valid questionnaires were retrieved. The OECD PISA 2015 School Questionnaire data were used to select topics that conformed to the definitions of the measurement variables. IBM SPSS Statistic 22.0 was used for descriptive statistics, exploratory factor analysis, and reliability testing. SPSS AMOS was used for validation of the structural equation model in terms of goodness of fit. The results validated the seven proposed hypotheses and indicated that the developed structural equations achieved good model fit. Relevant conclusions and recommendations are presented herein on the basis of the research findings.